2011
DOI: 10.1248/bpb.34.82
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of 5-Hydroxytryptamine (5-HT) Receptor Subtypes in 5-HT-Induced Vasoconstriction of the Distended Human Saphenous Vein as a Coronary Artery Bypass Graft

Abstract: Coronary artery bypass graft (CABG) surgery has been performed for about 40 years. In 1967, the technique of saphenous vein (SV) bypass grafting was introduced, followed 1 year later by the use of internal thoracic artery (ITA).1) Whereas ITA is the first-choice arterial graft, 2,3) SV still continues to be the most commonly used conduit vessel for CABG 4,5) because of ready availability and suppleness. One of the most serious problems in CABG surgery is that the bypass grafts often go into spasm after implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In fact, we observed that acetylcholine failed to induce vasodilation of the SV segments preconstricted with noradrenaline. 62) Furthermore, light and immunohistochemical microphotographs of the SV segment demonstrated that the venous wall was mainly composed of smooth muscle cells, and almost all endothelial cells were desquamated. 62) Thus, the endothelial 5-HT 1B receptor-mediated vasodilation may not occur and a selective 5-HT 1B receptor antagonist may act as merely a vasodilator in the SV graft.…”
Section: Saphenous Vein Graft Diseases Associ-ated With Coronary Artementioning
confidence: 99%
See 2 more Smart Citations
“…In fact, we observed that acetylcholine failed to induce vasodilation of the SV segments preconstricted with noradrenaline. 62) Furthermore, light and immunohistochemical microphotographs of the SV segment demonstrated that the venous wall was mainly composed of smooth muscle cells, and almost all endothelial cells were desquamated. 62) Thus, the endothelial 5-HT 1B receptor-mediated vasodilation may not occur and a selective 5-HT 1B receptor antagonist may act as merely a vasodilator in the SV graft.…”
Section: Saphenous Vein Graft Diseases Associ-ated With Coronary Artementioning
confidence: 99%
“…62) Furthermore, light and immunohistochemical microphotographs of the SV segment demonstrated that the venous wall was mainly composed of smooth muscle cells, and almost all endothelial cells were desquamated. 62) Thus, the endothelial 5-HT 1B receptor-mediated vasodilation may not occur and a selective 5-HT 1B receptor antagonist may act as merely a vasodilator in the SV graft. In our previous study, sarpogrelate or the 5-HT 1B receptor antagonist SB224289 partially inhibited, and the combination of these antagonists almost abolished the 5-HT-induced vasoconstriction in human SVs.…”
Section: Saphenous Vein Graft Diseases Associ-ated With Coronary Artementioning
confidence: 99%
See 1 more Smart Citation
“…Other 5-HT receptor families are heptahelical receptors coupled to G proteins (Gs, Go, Gi, Gq/11) and have diverse effectors. 5-HT 2A and/or 5-HT 1 receptor subtypes mediate 5-HT-induced vasoconstriction exclusively [6]. The 5-HT receptors mediating constriction in coronary arteries from different species are predominantly the 5-HT 2 receptor and, to a lesser extent, 5-HT 1 receptor [1], [7].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that in isolated human endothelium-denuded SVs, 5-HT 2A and 5-HT 1B receptors similarly contribute to 5-HT-induced vasoconstriction (24). The rings were treated with 300 μM L-NAME or L-NAME plus 100 nM wortmannin 15 min before the addition of 5-HT.…”
Section: Discussionmentioning
confidence: 99%